2009
DOI: 10.1227/01.neu.0000351773.74034.5e
|View full text |Cite
|
Sign up to set email alerts
|

A Successful Combined Endovascular and Surgical Treatment of a Cranial Base Mucormycosis With an Associated Internal Carotid Artery Pseudoaneurysm

Abstract: Aggressive multimodal therapy is imperative for late-stage rhinocerebral mucormycosis. Extensive resection of infected tissue combined with amphotericin B, atorvastatin, and hyperbaric oxygen seems to be the best course of management. If the internal carotid artery is involved, endovascular intervention is clearly an option to attain this goal. Further research and longer follow-up periods are required to better understand the long-term implications of endovascular coiling and hyperbaric oxygen therapy for rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…However, this patient had an unusual presentation, as parotid involvement due to zygomycosis has only been described once previously 5. Her inflammatory vasculitis and ensuing strokes from involvement of the carotid artery are recognized complications of zygomycosis, and in 1 case series of 41 patients with rhinocerebral mucormycosis, carotid involvement was seen in 31% of patients 6. After the punch biopsy of the patient's pinna showing nonseptated hyphae “reminiscent” of Mucor , why did her physicians delay administering amphotericin?…”
Section: Commentarymentioning
confidence: 79%
“…However, this patient had an unusual presentation, as parotid involvement due to zygomycosis has only been described once previously 5. Her inflammatory vasculitis and ensuing strokes from involvement of the carotid artery are recognized complications of zygomycosis, and in 1 case series of 41 patients with rhinocerebral mucormycosis, carotid involvement was seen in 31% of patients 6. After the punch biopsy of the patient's pinna showing nonseptated hyphae “reminiscent” of Mucor , why did her physicians delay administering amphotericin?…”
Section: Commentarymentioning
confidence: 79%
“…With development and gradual perfection in recent years, endovascular interventional therapy has been gradually taking the place of the traditional treatment methods for TICAP by virtue of its microtrauma and high recovery rate. This technique is the treatment of choice for TICAP; balloons and covered stents are frequently-used embolising materials (1)(2)(3)13,19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Intracranial findings include infarcts related to vascular thrombosis, mycotic emboli, and frontal lobe abscesses [172,173]. Alvernia et al reported a case of internal carotid artery pseudoaneurysm owing to skull base mucormycosis [174]. Additionally, Delbrouck and co-authors presented a patient with a carotid artery occlusion due to fulminant rhinocerebral mucormycosis [175].…”
Section: Mucormycosismentioning
confidence: 99%
“…Amphotericin B is the drug of choice for treatment of mucormycosis and is recommended that therapy should be started as soon as the diagnosis is confirmed. Hyperbaric oxygen therapy can also be given as adjuvant [174].…”
Section: Mucormycosismentioning
confidence: 99%